Google Translate Application for Simple Writing - Mildan Arsdan Fidinillah (Scope : Journal of English Language Teaching, 2022)
The common problem in English teaching to a group of Indonesian speakers is that the group has difficulty understanding to an English topic. Such as in tenses, traditionally most teachers have done their best to explain in simple English and provide numerous examples. There's nothing wrong with this approach. However, as many Indonesian-speaking English teachers probably know, it can be helpful to quickly explain the concept in Indonesian. Then the lesson can turn back to English. Consequently, it wastes time and not effective, a solution should be found. One of the solutions is the Google Translate where Google Translate offers the most powerful, free online translation tools available. This English teaching article focuses on using Google Translate to help out in difficult situations, as well as provide ideas on how to use Google Translate in class in lesson plans. This research tries to provide and share the strength and weaknesses of Google translate tool for writing learning. This research took some students from seventh semester of UNINDRA students as sample.  The methodology used was descriptive. This research took time for about four (4) months. The findings of this research point out that many people are helped by the benefit of the Google Translate application. Despite the weaknesses of it, they believe that the results of the translation are accurate as long as they revise the translations manually.